2019
DOI: 10.1186/s13148-019-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A facilitates KRAS signaling-regulated enhancer activity in an AP1-dependent manner in colorectal cancer cells

Abstract: Background ARID1A (AT-rich interactive domain-containing protein 1A) is a subunit of the BAF chromatin remodeling complex and plays roles in transcriptional regulation and DNA damage response. Mutations in ARID1A that lead to inactivation or loss of expression are frequent and widespread across many cancer types including colorectal cancer (CRC). A tumor suppressor role of ARID1A has been established in a number of tumor types including CRC where the genetic inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 76 publications
4
44
1
Order By: Relevance
“…We then performed motif enrichment analysis by using the AME algorithm [26] on each group of ATAC peaks. Interestingly, we found that the binding motifs of SRY, FOX family, CDX1, SOX5, etc., were enriched in the ATAC peaks with significantly increased accessibility in ARID1A-KO cells (Figure 5F, and Supplementary File 7), which is consistent with the results of a recent study showing ARID1A as a co-factor of AP-1 [27].…”
Section: Arid1a Knockout Alters Gene Expression Mainly By Modulating the Chromatin Accessibility Of Distal Regulatory Elementssupporting
confidence: 91%
“…We then performed motif enrichment analysis by using the AME algorithm [26] on each group of ATAC peaks. Interestingly, we found that the binding motifs of SRY, FOX family, CDX1, SOX5, etc., were enriched in the ATAC peaks with significantly increased accessibility in ARID1A-KO cells (Figure 5F, and Supplementary File 7), which is consistent with the results of a recent study showing ARID1A as a co-factor of AP-1 [27].…”
Section: Arid1a Knockout Alters Gene Expression Mainly By Modulating the Chromatin Accessibility Of Distal Regulatory Elementssupporting
confidence: 91%
“…Similarly, concomitant bi-allelic deletion of Arid1a in the Apc min mice significantly inhibited intestinal neoplasia [33]. In addition, CRISPR-mediated deletion of ARID1A in human colorectal cancer cells with KRAS mutations significantly reduced proliferation, accompanied by attenuation of MEK/ERK dependent transcriptional signaling [34]. ARID1A mutations also correlated with better survival in uterine corpus endometrial carcinoma [35].…”
Section: Discussionmentioning
confidence: 96%
“…Our RT-qPCR results showed that overexpression of candidate transcription factors E2F1, ELK1, NFκB, Oct4, Sp1 or STAT3 did not influence ZNF322A mRNA expression. However, it is still possible that other TF candidates, for example c-jun or c-myc, which has been shown to cooperate with mutated Kras 28 - 30 , may play a role in regulating ZNF322A transcription. Whether YY1 need additional TF or transcription co-regulators to drive ZNF322A transcription is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%